(untitled) (Вісник: Міжнародні відносини, 2024)
Remittances from migrant workers often act as a lifeline for many families and communities in developing countries that are in dire straits. Migrants’ remittances represent the monetary dimension of international migration. They can have a significant impact on poverty reduction and can finance economic growth in countries that host migrants. For many countries, remittances are a significant and stable source of funds, sometimes exceeding official development assistance or financial receipts from foreign direct investment. Despite the fact that remittances exceed official development assistance, it is worth considering that these are private funds, not public funds. Global estimates of migrant remittances include transactions beyond what is commonly considered remittances, as the statistical definition used to collect data on remittances is broader. Remittance flows often play a countercyclical role: that is, they persist during adverse events in recipient countries. Despite the COVID-19 crisis and political instability, the total volume of remittances continues to grow. Today, Ukraine is a donor country of labor migrants, and in the near future the flow of emigration will increase, which creates a threat of significant losses of the nation’s human capital, and lowers the country’s level of international competitiveness. Russia’s war against Ukraine has caused a major humanitarian disaster and refugee crisis. Ukraine continues to lose its population as a result of going abroad. This is explained by a combination of factors, in particular, Russia’s unprovoked aggression against Ukraine, inflation, political instability, corruption of all branches of government, lack of a culture of law enforcement. Since the beginning of the war, more than 8 million refugees have left Ukraine and remained in Europe, adding to the global number of Ukrainians living outside of Ukraine. The state is losing its human potential. In the context of the growing humanitarian crisis caused by Russia’s unprovoked aggression against Ukraine, remittances from Ukrainians to the EU are a vital way to provide for family and native livelihoods.